Education for All: Implementing Fun English Learning in Non-Formal Settings - Kuzairi Kuzairi (Literaturia: Journal of Linguistics, Literature, and Language Teaching, 2026)
The "Education for All" (EFA) initiative underscores the right to equitable quality education, yet children from low-income backgrounds often face barriers to acquiring global skills like English. This community service project aimed to implement and evaluate a Fun English Learning program at "Kelompok Belajar Anak Bangsa Mandiri," a non-formal educational setting in Banjarmasin, over six months. The program sought to create an enjoyable learning atmosphere and develop the basic English capacity of underprivileged children. Employing a qualitative descriptive method, the project integrated the SAVI (Somatic, Auditory, Visual, Intellectual) framework and the PAKEM (Participatory, Active, Creative, Effective, Joyful) model through thematic lessons, games, songs, and visual aids. Results demonstrated high levels of student enthusiasm, active participation, and significant improvement in foundational vocabulary and communication confidence. The findings indicate that a pedagogy of joy and engagement is not a luxury but a necessity for effective learning in marginalized contexts. The project concludes that community-based, non-formal education programs utilizing Fun English Learning approaches are a viable and powerful strategy to bridge the educational equity gap, fulfilling the promise of Education for All by ensuring no child is left behind in acquiring essential 21st-century skills.